Does firm size matter? evidence on the impact of the green innovation strategy on corporate financial performance in the automotive sector - Lin, Woon Leong; Cheah, Jun Hwa; Mohamed, Azali; Ho, Jo Ann; Yip, Nick (Elsevier, 2019)
In the past few years, there has been increasing awareness regarding the significance of the Green Innovation Strategy (GIS) in the academic and practical fields. Hence, it becomes important to determine the correlation between the GIS and the Corporate Financial Performance (CFP). This study attempted to determine the dynamic correlation between the GIS and the CFP, with regards to the firm size. For this purpose, this study has collected data for 163 international automotive firms, from the CSRHub database, for the period ranging between 2011 and 2017. Furthermore, we also used the dynamic panel data system, i.e., the Generalised Method of Moment (GMM) method, for estimating this relationship. The empirical results indicated that the GIS positively affected the CFP. Interestingly, we also uncovered that the firm size moderated the negative correlation between the GIS and the CFP. The small-sized firms showed higher green innovation investments return than the larger-sized firms, which indicated that these smaller firms were more prone to seek variation and visibility, for accessing better resources. Furthermore, due to the extensive scrutiny of the stakeholders, these small firms could generate higher profits. The implications for managers and the theories in this regard are then discussed.